Analisis Peran Pendidikan dalam Membangun Kesadaran Anti Korupsi di Kelurahan Penjaringan Asri Kelas G150 UPN ”Veteran” Jawa Timur - Sutanto, Patrick Nicholas; Fatihunniam, Adib (Cahaya Ilmu Bangsa Institute, 2024)
The research methods employed include descriptive, qualitative, and interdisciplinary research to depict the phenomenon of corruption and the role of education in fostering anti-corruption awareness. Curriculum adaptation, teacher involvement, and collaboration among schools, parents, and communities are pivotal in shaping an environment supportive of anti-corruption education. The use of technology and media is also crucial for disseminating anti-corruption messages widely. Through this approach, anti-corruption education can become more effective in shaping awareness and behavior among the younger generation and mobilizing community support in combating corruption.